Evaluation of faecal glucocorticoid monitoring as a non-invasive assessment of stress in captive white rhinoceros (Ceratotherium simum) after ACTH stimulation - Swan, Gerry E. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.